Impact of Commodity Price and Exchange Rate on IHSG with Geopolitics as Moderation - Abdul Hayyi Numan; Aliansyah, Yusron; Abdul Haris (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine the influence of world gold prices, world oil prices, world coal prices, and exchange rates on the Indonesian composite stock index. The tests of the ponder are Indonesia's world oil prices, world gold prices, world coal prices, trade rate, geopolitical chance record, and composite stock prices for Indonesia, data from www.investing.com and www.policyuncertainty.com January 2020 to December 2023. The method used to analyze the data in this research is multiple regression analysis and residual tests for moderator variables. Through F test analysis it is known that simultaneously all variables X have a significant influence on the Indonesian Composite Stock Price Index at the 5% level. Based on these results, the research hypothesis is accepted. Furthermore, through t-test analysis (subtest), the variables of world gold prices, world oil prices, world coal prices, and exchange rates have a partially significant influence on the Indonesian Composite Stock Price Index at a confidence level of 100. It turns out to be 95% (a = 5%). It can be concluded that changes in these variables influence changes in the Indonesian composite stock index. In addition, geopolitical variables cannot moderate the relationship between all variables X and Y. This shows that geopolitical factors do not play a significant role in this context. The variation in the Indonesian Composite Stock Price Index of 88.0 can be explained by combining all variables X. The remaining 12.0% can be explained by other factors not included in the estimation model.